(3eNJUQ GdJGQjN ef Chd GdReGf Edi efJgi OhdI Hfi GdYHGSs - (3XgjQ GdOjf Ydj Hf eMeO Hf eMehO GdcGRQhfj GdHZOGOj, GdcGRQhfj,J (B697 (3g` s
(3ChdgG (B:s
(3Chdg HYO GdHSedI (B: (3PcQ eOI GdReGf heG eVi efg s
(3BNQgG (B:s
(3hGfbVJ GdOhdI GdYHGSjI , aSHMGf ef dG jfbVi edcg hdG jRhd s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B334s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B134 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs